1989
DOI: 10.1111/1523-1747.ep12277095
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil Stimulates Mouse Vibrissae Follicles in Organ Culture

Abstract: Minoxidil, a potent vasodilator, stimulates the growth of terminal hair from vellus or miniaturized follicles in balding scalp. To study minoxidil's action on isolated follicles we developed and validated an organ culture system using mouse whisker follicles. Control follicles cultured without minoxidil showed macroscopic changes including kinking of the hair shafts and bending of the follicles. Necrosis was evident in the differentiating epithelial elements forming the cuticle, cortex, and inner root sheath. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 12 publications
2
67
0
2
Order By: Relevance
“…25) Buhl et al reported that minoxidil stimulates hair growth of mouse vibrissae follicles in organ culture. 26) In a whole skin piece culture system from 4-week-old mice, 27) it also demonstrated that minoxidil promoted hair follicle elongation. Minoxidil causes telogen hair follicles to enter the anagen phase, and prolongs the anagen period, and thus increases hair follicle size.…”
Section: Discussionmentioning
confidence: 95%
“…25) Buhl et al reported that minoxidil stimulates hair growth of mouse vibrissae follicles in organ culture. 26) In a whole skin piece culture system from 4-week-old mice, 27) it also demonstrated that minoxidil promoted hair follicle elongation. Minoxidil causes telogen hair follicles to enter the anagen phase, and prolongs the anagen period, and thus increases hair follicle size.…”
Section: Discussionmentioning
confidence: 95%
“…The hair follicle culture method has several advantages in hair research, including the measure of hair-fiber elongation and maintenance of normal architecture. 39,40) In this study, we isolated rat vibrissa follicles from 23-d old rats and found that the S. muticum extract significantly promoted hair-fiber length in cultured rat vibrissa follicles. By the way, we couldn't find the dose-dependency of the S. muticum extract on the elongation of hair-fiber length.…”
Section: Discussionmentioning
confidence: 87%
“…To identify new hair-growing agents, cultures of hair fol- licles from several species such as human, 11,32) rat, 39) sheep 51) and mouse 40,52) were developed. The hair follicle culture method has several advantages in hair research, including the measure of hair-fiber elongation and maintenance of normal architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the utility o f this human follicle culture system for pharmacological studies is unclear. In contrast, Buhl et al [12] have shown that minoxidil stimulates both DNA and protein synthesis in mouse whisker follicles in organ culture. We extended this finding to show that pinacidil and diazoxide, potassium channel openers whose therapeutic use has also been associated with hypertricho sis, also stimulate DNA synthesis in this mouse follicle culture system [ 13], These find ings thus support the utility o f cultured mouse whisker follicles as a model for testing com pounds for potential hypertrichotic activity.…”
Section: Introductionmentioning
confidence: 83%